Competitive Adsorption of Ions at the Oil-Water Interface A Possible Mechanism Underlying the Separation Selectivity for Liquid-Liquid Solvent Extraction - Sun, Pan (Langmuir : the ACS journal of surfaces and colloids, 2018)
Adsorption, especially competitive adsorption of ions at the interfaces, governs a wealth of physicochemical processes. Understanding the mechanism behind these interfacial behaviors is crucial for developing novel strategies to intensify reactions or transfer processes. Herein, as an example, we found that in the case of liquid-liquid transport of V(V) and Cr(VI) ions, the competitive adsorption of V(V) and Cr(VI) ions against coexisting SO42- ions at the oil-water interface exhibits a significant impact on the selective separation behaviors of V(V) and Cr(VI) ions. The transport of Cr(VI) ions would be hindered by adding Na2SO4 into the aqueous solutions because of the competitive adsorption of SO42- ions at the interface being stronger than that of Cr(VI) ions, whereas the transport of V(V) ions would not be affected because of the stronger affinity of V(V) ions to the interfaces compared to that of SO42- ions. The present work provides new inspirations for developing efficient strategies to improve the separation efficiency of target ions with similar physic-chemical properties by regulating their adsorption behaviors at the interface. It is beneficial to get a deeper understanding into the microscopic nature of competitive adsorption behaviors of ions at interfaces from the interface-molecular level